'Show me the money and the party!' – variation in Facebook and Twitter adoption by politicians. Issue 8 (3rd August 2018) - Quinlan, Stephen; Gummer, Tobias; Roßmann, Joss; Wolf, Christof
ABSTRACT: Our study explores the adoption of Facebook and Twitter by candidates in the 2013 German Federal elections. Utilizing data from the German Longitudinal Election Study candidate survey fused with data gathered on the Twitter and Facebook use of candidates, we draw a clear distinction between Facebook and Twitter. We show that adoption of both channels is primarily driven by two factors: party and money. But the impact of each plays out differently for Facebook and Twitter. While the influence of money is homogenous for Facebook and Twitter with the more resources candidates have, the more likely they are to adopt, the effect is stronger for Facebook. Conversely, a party's impact on adoption is heterogeneous across channels, a pattern we suggest is driven by the different audiences Facebook and Twitter attract. We also find candidates' personality traits only correlate with Twitter adoption, but their impact is minimal. Our findings demonstrate that social media adoption by politicians is far from homogenous, and that there is a need to differentiate social media channels from one another when exploring motivations for their use.